2012
DOI: 10.1159/000339158
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperglycemia Corrected by IGF-I (Increlex®) in Laron Syndrome

Abstract: Background: Laron syndrome is caused by a mutation in the growth hormone (GH) receptor and manifests as insulin-like growth factor-I (IGF-I) deficiency, severe short stature, and early hypoglycemia. We report a case with postprandial hyperglycemia, an abnormality not reported previously. Postprandial hyperglycemia was due to chronic IGF-I deficiency, and was reversed by IGF-I replacement therapy. Methods: A Moroccan girl referred for short stature at 7 years and 8 months of age had dwarfism [height, 78 cm (–9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…GH can bind either defectively to the ectodomain of GHR or there is diminished effectiveness in dimerization of the receptor after the hormone occupies receptor leading to block in signalling cascade which finally results in decreased IGF-1 and ultimately holds up the mitogenic effects of GH. [2][3][4][5][6] Hence in Laron syndrome though the growth hormone levels are high IGF-1 levels are remarkably low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GH can bind either defectively to the ectodomain of GHR or there is diminished effectiveness in dimerization of the receptor after the hormone occupies receptor leading to block in signalling cascade which finally results in decreased IGF-1 and ultimately holds up the mitogenic effects of GH. [2][3][4][5][6] Hence in Laron syndrome though the growth hormone levels are high IGF-1 levels are remarkably low.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis with respect to final height in males is 116 to 142 cms and Females is 108 to 136 cms. 5 Despite the appearance of premature aging signs, like thin and wrinkled skin, patients with LS have a long life. 4,11 There is delay in attainment of puberty by 3-7 year and does not display the typical pubertal growth spurt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laron et al [3] demonstrated relative insulinopenia in young adults with GHI following chronic IGF-1 deprivation, and there are reports of patients with GHI developing insulin resistance [25]. The youngest age at which postprandial hyperglycaemia has been reported is 7.7 years, although this was measured before treatment [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) has approved clinical use of mecasermin, a recombinant human IGF-I analog intended for subcutaneous application 50,51 and also of mecasermin rinfabate, a binary complex of equimolar IGF-I and IGFBP-3 (ref. 52,53 ).…”
Section: Practical Aspects Of Rigf-i Therapymentioning
confidence: 99%